Sosialisasi Penggunaan Lean Six Sigma dengan Konsep DMAIC untuk Menghilangkan Muda Proses Pengambilan Baut Lebih dari Standar - Hertyoso Nursasongko; Niman Niman; Lutfy Eka Biardhian (Jurnal Ilmiah Wahana Pendidikan, 2022)
One method for improving quality is Lean Six Sigma with the concept of DMAIC (Define, Measure, Analyze, Improve and Control). This is oriented to analyze mismatches of production activities. This research and development aims to improve the quality of the FWA LH post parking brake bolt products. This is because the occurrence of problems that are not in accordance with work standards. The results of research and development show there are 2 main problems. From the results of the define step analysis, it can be seen: workers take bolts by manually and are not suitable for the amount needed. At this step it is supported by the 5W+1H concept. The results of the measure step analysis can be known through the fishbone diagram. This will know the beginning of the problem (Man, Material, Machine, Method and Environment). Analyze step results are used by FMEA (Failure Mode and Effect Analysis). With the aim of identifying problems and ranking every failure mode with RPN (Risk Priority Number). Furthermore, the results of the improvement step analysis are used by APFM (Action Planning for Failure Mode). With the aim of providing recommendations in the form of solutions from FMEA results. Then as a result of the control step analysis for periodic checks.